Infarct‐like myocarditis with coronary vasculitis and aneurysm formation caused by Epstein–Barr virus infection - Cristina Chimenti; Romina Verardo; Claudia Grande; Marco Francone; Andrea Frustaci (ESC Heart Failure)
Abstract Myocardial infection by Epstein–Barr virus (EBV) may manifest with inflammatory cardiomyopathy, coronary syndrome X, and rarely with infarct‐like myocarditis. The aim of the report is to describe a case of myocardial EBV infection causing acute myocarditis with heart failure, necrotizing coronary vasculitis, and multiple left ventricular (LV) aneurysms. A 67‐year‐old woman presented with fever, chest pain, and heart failure. She underwent non‐invasive cardiac studies including electrocardiography, 2D‐echocardiography, cardiac magnetic resonance, hematochemical exams with Troponin T determination, and invasive studies including cardiac catheterization, coronary angiography, and LV endomyocardial biopsy. Five endomyocardial samples were processed for histology and immunohistochemistry for inflammatory cells characterization and detection of viral antigens. Two additional frozen samples were evaluated by real‐time polymerase chain reaction for the presence of cardiotropic viral genomes. Routine laboratory tests revealed the presence of elevated white blood cells (17 000 103/μL) and increased Troponin T. Electrocardiogram showed sinus tachycardia with ST elevation in V2–V5. Two‐dimensional echocardiography showed normal LV dimension with reduced LV contractility (LVEF = 40%) with mild pericardial effusion. Cardiac magnetic resonance revealed the presence of a micro‐aneurism in the inferior LV wall, a diffuse oedematous imbibition of LV myocardium suggested by hyper‐intensity of T2 mapping, and increased fibrosis as suggested by areas of late gadolinium enhancement signals. Coronary arteries were normal while several micro‐aneurysms were observed at LV angiography. At histology, a lymphocytic myocarditis with necrotizing coronary vasculitis sustained by a positive real‐time polymerase chain reaction for EBV, detectable in cardiomyocytes and inflamed intramural vessels by positive immunohistochemistry for EBV latent membrane protein 1 antigen, was observed. Myocardial EBV infection is an unusual cause of acute heart failure and cardiac aneurysms, increasing the risk of electrical instability, cardiac perforation, and sudden death.